Tính (bằng định nghĩa) đạo hàm của các hàm số sau:
a) y = {x^2} - x tại {x_0} = 1;
b) y = - {x^3} tại {x_0} = - 1.
f’\left( {{x_0}} \right) = \mathop {\lim }\limits_{x \to {x_0}} \frac{{f\left( x \right) - f\left( {{x_0}} \right)}}{{x - {x_0}}} nếu tồn tại giới hạn hữu hạn \mathop {\lim }\limits_{x \to {x_0}} \frac{{f\left( x \right) - f\left( {{x_0}} \right)}}{{x - {x_0}}}
Advertisements (Quảng cáo)
a) f’\left( 1 \right) = \mathop {\lim }\limits_{x \to 1} \frac{{f\left( x \right) - f\left( 1 \right)}}{{x - 1}} = \mathop {\lim }\limits_{x \to 1} \frac{{{x^2} - x}}{{x - 1}} = \mathop {\lim }\limits_{x \to 1} \frac{{x\left( {x - 1} \right)}}{{x - 1}} = \mathop {\lim }\limits_{x \to 1} x = 1
Vậy f’\left( 1 \right) = 1
b) f’\left( { - 1} \right) = \mathop {\lim }\limits_{x \to - 1} \frac{{f\left( x \right) - f\left( { - 1} \right)}}{{x + 1}} = \mathop {\lim }\limits_{x \to - 1} \frac{{ - {x^3} - 1}}{{x + 1}} = \mathop {\lim }\limits_{x \to - 1} \frac{{ - \left( {x + 1} \right)\left( {{x^2} - x + 1} \right)}}{{x + 1}} = \mathop {\lim }\limits_{x \to - 1} \left( {{x^2} - x + 1} \right) = 3
Vậy f’\left( { - 1} \right) = 3